Effects of High‐ and Low‐Fat Meals on the Pharmacokinetics of Ozanimod, a Novel Sphingosine‐1‐Phosphate Receptor Modulator - Tran, Jonathan Q. (Clin Pharmacol Drug Dev, 2017)
Ozanimod (RPC1063) is an oral selective modulator of the sphingosine‐1‐phosphate 1 and 5 receptors under development for the treatment of relapsing multiple sclerosis and inflammatory bowel disease. The effects of high‐fat and low‐fat meals on the pharmacokinetics (PK) of a single oral dose of ozanimod were evaluated in 24 healthy volunteers in a randomized, open‐label crossover trial. Each subject received a 1‐mg dose of ozanimod hydrochloride under 3 meal conditions (fasted, high‐fat, and low‐fat), each separated by 7 days. Mean plasma concentration–time profiles for ozanimod and its active metabolites (RP101988 [major], RP101075 [minor]) were similar under all 3 conditions. Moreover, all PK parameters for ozanimod, RP101988, and RP101075 were similar under the 3 meal conditions. The 90% confidence intervals (CIs) for the ratios of geometric least‐squares mean (fed/fasted) were within the equivalence limits of 0.80 to 1.25 for area under the concentration–time curve from time 0 to infinity (AUC(0–∞)) and maximum plasma concentration (C(max)) for ozanimod, RP101988, and RP101075, except for the high‐fat effect on RP101075 C(max) (90%CI, 0.76–0.88). Given this lack of a food effect on the exposure of ozanimod and its active metabolites, ozanimod can be taken without regard to meals.